Pengembangan Website Informasi Hama Wereng - Arief Budiman; Pradityo Utomo (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
In Indonesia, rice is still an essential commodity. Besides as a crop producing staple food for rice, also as a source of eyes the primary search for farmers. Problems that are often experienced by farmers are the threat of pest attacks. If not handled quickly and correctly suffered a massive loss, it can even cause a failed harvest finally harming farmers. In Madiun Regency, the total rice fields are planted hopper infestation before the 2017 rainy season harvest reaching 223 hectares covering Pilangkenceng Subdistrict, Wonoasri, Balerejo, Sawahan, Mejayan, Saradan, and Wungu. So far to suppress attacks Planthopper pests, farmers, give stimulant pesticides to plants that if Improper handling will interfere with health. The best solution is to recognize the initial attack of pests so that the level of attack on plants can be minimized. The limited knowledge and skills of partner farmers in identifying their paddy plants early makes farmers prefer the fast way by spraying pesticides. This Community Service aims to motivate farmers to avoid using pesticides by providing quick and easy and attractive solutions in early detection rice crop pests. To facilitate farmers in detecting pest attacks, a website was developed which contained information about planthopper pest attacks and how to overcome them by using biological agents. Website developed can be used by farmers by accessing it through a browser on a computer device or smartphone device.Keywords : Website, Pest, Rice, Farmers.Â